Cervical cancer benefits from trabectedin combination with the β-blocker propranolol: in vitro and ex vivo evaluations in patient-derived organoids - Di Fonte, Roberta; Strippoli, Sabino; Garofoli, Marianna; Cormio, Gennaro; Serratì, Simona; Loizzi, Vera; Fasano, Rossella; Arezzo, Francesca; Volpicella, Mariateresa; Derakhshani, Afshin; Guida, Michele; Porcelli, Letizia; et al. (Frontiers in Cell and Developmental Biology, 2023)
Background: Cervical cancer (CC) is characterized by genomic alterations in DNA repair genes, which could favour treatment with agents causing DNA double-strand breaks (DSBs), such as Trabectedin. Hence, we evaluated Trabectedin capability to inhibit CC viability, using ovarian cancer (OC) models as reference. Since stress hormones promote gynaecological cancers and may hinder the efficacy of treatment, we investigated the potential of targeting β-adrenergic receptors (β-ARs) with Propranolol to enhance Trabectedin efficacy and change tumor immunogenicity. Methods: OC cell lines Caov-3 and SK-OV-3 and CC cell lines HeLa and OV2008 and patients-derived organoids (PDOs) were used as study models. MTT and 3D cell viability assays were used for drug(s) IC50 determination. The analysis of apoptosis, JC-1 mitochondrial membrane depolarization, cell cycle and protein expression were performed by flow cytometry. Cell target modulation analyses were carried out by gene expression, western blot, immunofluorescence and immunocytochemistry. Results: Trabectedin reduced the proliferation of both CC and OC cell lines and notably of CC patient-derived organoids (PDOs). Mechanistically, Trabectedin caused DNA double-strand breaks (DSBs) and S-phase cell cycle arrest. Despite DNA DSBs, cells failed the formation of RAD51 foci and underwent apoptosis. Under norephinephrine stimulation, Propranolol enhanced Trabectedin efficacy further reducing cell DNA-repair proficiency and increasing p53-dependent apoptosis through the involvement of mitochondria, Erk1/2 activation and the increase of inducible COX-2. Notably, Trabectedin and Propranolol affected the expression of PD1 in CC and OC cell lines. Conclusions: Overall, our results show that CC is responsive to Trabectedin and provide reliable evidence that could benefit CC treatment options and pointed out that combined treatment offset Trabectedin resistance caused by β-adrenergic receptor activation in both ovarian and cervical cancer models.